FOXP3 and HER-2/ErbB2 in Breast Cancer: Finding Regulatory Links (Medico Legal Update, 2020)
The transmembrane tyrosine kinase receptor, HER2/ErbB2, has been a subject of many studies owing to itspredictive and prognostic values and its being a target of antibody-mediated treatment. Retrospective evidencestrongly proposes that the over expression of HER2 is related to reduced disease free and overall survival innode positive and perhaps also node negative breast cancers. Prospective attempts showed that antibodiesto HER2 can form tumor responses in advanced breast cancer women which overexpress this molecule.The existence of forkhead box protein 3 (FOXP3) in cells of breast cancer is a subject of debate. We havesystematically analyzed the FOXP3 expression in 20 breast carcinoma samples at transcript levels. Recentprogresses in understanding breast cancer crosstalk, homing processes, tumor cell dormancy, premetastaticniche formation and finally recognition of their micromilieu cytokines, growth factors and chemokinesmightprovide the foundation of developing targeted treatment plans potentially rendering primary carcinomas andtheir metastases more responsive to chemotherapies. The current review has focused on the deep connectionsbetween HER-2 and FoxP3 in context of considering the determination of both of these molecules togetherto rationalize or more personalize the future research directions leading to better treatment for women withbreast carcinoma.